Composite Material Engineering Analysis Based on Circular Economy for the Conservation of Interior Ornaments and Traditional Balinese Architecture - Jaya, I Kadek Prana; Dewi, Ni Made Emmi Nutrisia (International Journal of Engineering, Science and Information Technology, 2025)
This study examines the engineering and application of sustainable composite materials as an alternative to traditional Balinese architectural ornaments through a comparative analysis of four material types: fiberglass, precast concrete, glass fiber-reinforced cement (GRC), and artificial sandstone. The scarcity of natural materials, growing ecological pressures, and the demand for economic efficiency and ease of production have driven the exploration of engineered materials that can represent Balinese architecture's aesthetic, symbolic, and spiritual values. The research employs a descriptive-qualitative methodology involving field observations, in-depth interviews with local artisans, and an analysis of each material's technical and cultural characteristics. Fiberglass and GRC stand out for their form flexibility and suitability for mass production, while precast concrete offers superior structural durability and long-term maintenance efficiency. Meanwhile, community-driven innovations in artificial sandstone exhibit strong potential for preserving traditional values while addressing contemporary sustainability challenges. The findings suggest that no single material emerges as universally superior; therefore, material selection should be context-dependent, considering both economic feasibility and cultural compatibility. The study concludes that integrating material innovation into traditional architecture must be grounded in circular economy principles, active community participation, and a deep understanding of vernacular values. These insights are expected to serve as a strategic reference for material selection in preserving Balinese cultural heritage while supporting the contextual and competitive development of the local creative industry within the Southeast Asian region.